(untitled) (Imagens da Educação, 2023)
This study aimed at investigating the types of writing tasks produced by Saudi EFL learners. It also aimed at exploring the writing challenges encountered by those students. The sample of this study consists of (261) students enrolled in ENG (011). The students were randomly chosen from three different colleges: college of business, college of medicine, and college of engineering. The researcher used a questionnaire with (13) items asking about the challenges faced by the students during writing tasks. The results of this study revealed that the most frequently writing tasks produced by the students were essays for exams, synthesis, and reflection papers. The results also revealed that ‘organizing paragraphs’, ‘using proper connections and transitions’, and ‘inability to keep writing flow’ were the most frequent challenges of writing tasks reported by the students. The present study provided some recommendations and pedagogical implications for policymakers and curriculum designers to take action in an attempt to avoid or lessen these challenges.